IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH ALADIN MOVIES IN ONE OF PRIVATE IN CIMAHI INSTITUTES - Reza Azhari; Silpia Rahayu (PROJECT (Professional Journal of English Education), 2023)
Vocabulary is an essential element in learning English. Besides learning four basics in English, the learner must master vocabulary, which is include one of the macro-skills in English. The article aims to discuss about how movie Aladin can improving vocabulary mastery for student who can use in daily activity. By the reason of restricted understanding used there is using the same vocabulary, thus through movie the student can get new vocabulary that can be directly implemented in daily life. Since it is believed that vocabulary is one of important thing to learn before we learn the other basic of English learning. The method using qualitative research for this research. Fortunately, the research subject in one of private campus in IKIP Siliwangi consisting of one male and nine female students. The instrument used was a questionnaire with 10 question. The details are revealed only from students in class A3 2017 English education department. The implication of the researcher showed that there is relevant between vocabulary learning through movie. It showed that 3 people on the subject said the vocabulary in the movie was very helpful and 7 people said they did not understand the vocabulary in the movie. Keywords:  Vocabulary Skill; Movie; Teaching